The Effect Of Work Environment And Job Characteristics On Turnover Intention With Job Satisfaction As A Mediating Variable at PT Bank Lampung - Vera Monica; Ayi Ahadiat; Keumala Hayati (Journal of Social Research, 2024)
The role of human resources is very important for company productivity. Factors such as work environment, job characteristics, and job satisfaction are important factors to emphasize employee turnover intention in the company. This study aims to determine the influence of the work environment and job characteristics on turnover intention, through job satisfaction among PT Bank Lampung workers. The data source in this research is primary data. Data collection was carried out through questionnaires to 245 respondents who were selected based on the Stratified Random Sampling technique and processed using AMOS software. The results of this research support the first hypothesis that the work environment has a positive and significant effect on job satisfaction of PT Bank Lampung workers, supports the second hypothesis that job characteristics have a positive and significant effect on job satisfaction of PT Bank Lampung workers, the results of this research also support the third hypothesis, namely that the work environment has a negative and significant effect on turnover intention. The fourth hypothesis in this study that job characteristics have a negative and significant effect on turnover intention is not supported. Furthermore, the results of this research also support the fifth hypothesis that job satisfaction has a negative and significant effect on turnover intention, support the sixth hypothesis that job satisfaction mediates the influence of the work environment on turnover intention, supports the seventh hypothesis that job satisfaction mediates the influence of job characteristics on turnover intention. Suggestions that can be given to PT. Bank Lampung are the company needs to explore whether employees who spend low working hours have sufficient access to training, skills development and work experience that can improve their qualifications and motivation. Companies need to review the level of employee involvement in decision making in the work environment, observe the leadership style of employees' direct superiors, the effectiveness of organizational communication, especially regarding employee involvement in the decision making process. Companies should also research further the factors that influence the level of employee salary satisfaction and need to review existing employee development programs to help employees adapt to the desired job position, analyze further whether there are deficiencies in training or development programs that hinder the employee adaptation process.